Case report: MELAS and concomitant presumed antiphospholipid antibody syndrome in an adult woman - Nouduri, Sirisha; Padmanabhan, Rajiv; Hicks, Richard; Abbott, Mary-Alice; O'Brien, Dennis; Schlaug, Gottfried (Frontiers in Neurology, 2022)
Mitochondrial encephalomyopathy, lactic acidosis, stroke-like episodes, and other features (short stature, headaches, seizures, and sensorineural hearing loss) constitute characteristics of MELAS syndrome. MELAS is a rare condition due to mutations in maternally inherited mitochondrial DNA with levels of heteroplasmy possibly related to late adulthood presentation1,3,4. A previously reported MELAS case coexisted with presumed Antiphospholipid Antibody Syndrome (APLAS), but the connection between MELAS and a potential APLAS is unclear2. A 29-year-old woman presented with mild right-sided sensorimotor symptoms and mixed aphasia in November 2021. She presented again in May 2022 for unrelenting headaches and was found to have a new right hemisphere syndrome with mild left-sided sensorimotor symptoms, hemineglect, and anosognosia. Characteristic lab and imaging studies were obtained. During the first presentation (October 2021), the discovery of anticardiolipin IgM antibodies (aCL) (and their replication 3 months later) led to a diagnosis of APLAS, and Warfarin was initiated. During the second admission (May 2022), a new stroke-like lesion on the right hemisphere with characteristic features not suggestive of ischemia was detected, which led to a diagnosis of MELAS (m3243A>G mutation). Although MELAS and APLAS could co-exist, alternatively it is possible that antiphospholipid antibodies might be generated when the strongly anionic Cardiolipin-Hydroperoxide from the inner mitochondrial membrane, is exposed to immune component cells upon cell lysis. Thus, the presence of aCL in patients with stroke-like lesions might masquerade as an APLAS, but should probably be questioned if only aCL are repeatedly found and imaging findings are not characteristic for ischemic lesions.